Effects of swift heavy ion irradiation and annealing on the microstructure and recrystallizationof SiC pre-implanted with Sr ions - Abdelbagi, H. A. A.; Jafer, T. A. O.; Skuratov, V. A.; Njoroge, E. G.; Mlambo, M.; Hlatshwayo, T. T.; Malherbe, J. B. (Frontiers in Nuclear Engineering, 2022)
Polycrystalline SiC wafers were implanted with 360 keV strontium (Sr) ions at room temperature (RT) to a fluence of 2×1016 cm−2. Some of the implanted samples were irradiated with xenon (Xe) ions of 167 MeV to a fluence of 3.4×1014 cm−2 and 8.4×1014 cm−2 at RT. The as-implanted and implanted then irradiated samples were vacuum annealed (isochronally) at temperatures ranging from 1100 to 1400 ˚C in steps of 100 ˚C for 5 h. Annealing induced modification of the microstructure of the implanted and swift heavy ions (SHIs) irradiated SiC was studied by Raman spectroscopy, scanning electron microscopy (SEM) and Rutherford backscattering spectrometry (RBS). Sr ions bombardment caused formation of an amorphous layer in SiC, while irradiation by Xe ions led to partial recrystallization of the amorphized layer. After annealing at 1100 ˚C, the samples with low Sr retained ratio showed full recrystallization, while the samples with high Sr retained ratio showed poor recrystallization. This suggests that the presence of Sr within the implanted region inhibited the recrystallization of SiC. Annealing of the as-implanted samples at temperatures from 1100 ˚C and 1200 ˚C resulted in larger average crystal size compared to the SHIs irradiated samples annealed in the same temperature range. The difference in the average crystal sizes between the as-implanted and SHIs irradiated samples was due to the differences in the nucleation rate per amorphous area in the two samples. Raman spectroscopy results showed that the intensity of the LO mode of SiC increases with increasing crystal size. However, several factors such as pores and defects in SiC play a role in the decrease of the LO mode intensity of SiC (even if the average crystal size is large).